2022
DOI: 10.3390/nano12234153
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Powered Reverse Water Gas Shift Reaction Catalysed by Plasmonic Au/TiO2 Nanocatalysts: Effects of Au Particle Size on the Activity and Selectivity

Abstract: This study reports the low temperature and low pressure conversion (up to 160 °C, p = 3.5 bar) of CO2 and H2 to CO using plasmonic Au/TiO2 nanocatalysts and mildly concentrated artificial sunlight as the sole energy source (up to 13.9 kW·m-2 = 13.9 suns). To distinguish between photothermal and non-thermal contributors, we investigated the impact of the Au nanoparticle size and light intensity on the activity and selectivity of the catalyst. A comparative study between P25 TiO2-supported Au nanocatalysts of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Other metals, such Ru and Ni have shown a strong selectivity towards CH 4 production [7a,d,h,15] . Recently, our group has reported plasmonic Au nanoparticles supported on TiO 2 that promote the rWGS reaction under sunlight irradiation without any external heating in a batch process [7e,f] . We reported a maximum CO initial production rate of 429 mmol ⋅ g Au −1 ⋅ h −1 (8525 mmol ⋅ m −2 ⋅ h −1 ) with a selectivity of 98% and an apparent quantum efficiency of 4.7% using mildly concentrated sunlight (1.44 W ⋅ cm −2 =14.4 suns) in a batch process.…”
Section: Introductionmentioning
confidence: 88%
“…Other metals, such Ru and Ni have shown a strong selectivity towards CH 4 production [7a,d,h,15] . Recently, our group has reported plasmonic Au nanoparticles supported on TiO 2 that promote the rWGS reaction under sunlight irradiation without any external heating in a batch process [7e,f] . We reported a maximum CO initial production rate of 429 mmol ⋅ g Au −1 ⋅ h −1 (8525 mmol ⋅ m −2 ⋅ h −1 ) with a selectivity of 98% and an apparent quantum efficiency of 4.7% using mildly concentrated sunlight (1.44 W ⋅ cm −2 =14.4 suns) in a batch process.…”
Section: Introductionmentioning
confidence: 88%
“…The light‐driven process obtained higher activity and selectivity in comparison to thermal reference experiments. Previous research based on experimental and theoretical analysis supported that the reaction was promoted by a synergistic contribution of (photo)thermal and photochemical processes [125,126] . Upadhye et al .…”
Section: Catalysts For Solar‐driven Co2 Reductionmentioning
confidence: 94%
“…Previous research based on experimental and theoretical analysis supported that the reaction was promoted by a synergistic contribution of (photo)thermal and photochemical processes. [125,126] Upadhye et al ruled out localized heating effects based on reported literature [127] and the apparent activation energies found. [124] Here, the increase in productivity was predominantly attributed to a reduction in inhibition due to surface coverage of adsorbed species, which could be caused by either hot electrons or intense electromagnetic fields around the gold nanoparticles.…”
Section: Strongly Plasmonic Metal Nanoparticle Based Catalystsmentioning
confidence: 99%
“…[22][23][24] To date, significant strides have been made in the development and evaluation of catalysts and reactor systems for the hydrogenation of carbon dioxide. [25][26][27][28][29][30][31][32][33] However, direct comparison of the performance and efficacy of these catalysts remains challenging due to the absence of standardized operational procedures. In this endeavor, we aim to tackle these challenges by introducing an automated, integrated, and modular reactor system.…”
Section: Introductionmentioning
confidence: 99%